2013
DOI: 10.1111/gcbb.12080
|View full text |Cite
|
Sign up to set email alerts
|

Mass‐flowering crops increase richness of cavity‐nesting bees and wasps in modern agro‐ecosystems

Abstract: Considerable uncertainties exist on how increased biofuel cropping affects biodiversity. Regarding oilseed rape, the most common biofuel crop in the EU, positive responses of flower-visiting insects to plentiful nectar and pollen seem apparent. However, previous investigations on this insect guild revealed conflicting results, potentially because they focused on different taxonomic groups representing a narrow range of ecological traits and considered only short time periods. Here, using trap nests in landscap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 21 publications
1
72
0
1
Order By: Relevance
“…As Osmia bicornis is often a dominant trap‐nesting species (e.g. Diekötter et al., ), we performed the same analysis considering whether season variations in nest colonization differed between O. bicornis populations and non‐ O. bicornis species, separately. In these cases, field boundary ID was also included in the model as a random factor.…”
Section: Methodsmentioning
confidence: 99%
“…As Osmia bicornis is often a dominant trap‐nesting species (e.g. Diekötter et al., ), we performed the same analysis considering whether season variations in nest colonization differed between O. bicornis populations and non‐ O. bicornis species, separately. In these cases, field boundary ID was also included in the model as a random factor.…”
Section: Methodsmentioning
confidence: 99%
“…Oilseed rape, as a mass flowering crop, can provide food resources for pollinating insects but only during a limited period of the year [69]. A sustainable benefit for pollinators can only be achieved when a continuous flower supply is ensured through supplementary habitats in the landscape [29].…”
Section: A1: First-generation Energy Crop Production On Productive Agmentioning
confidence: 99%
“…These studies included the spatial and temporal aspects of bioenergy-driven land-use change and/or adaptations of the whole farming system (e.g. [25][26][27][28][29][30]). …”
Section: Introductionmentioning
confidence: 99%
“…Mass-flowering OSR fields were found to have a strong positive influence on the abundance of generalist solitary bees (Holzschuh et al 2013) and bees of the genus Osmia have been shown to be efficient pollinators of OSR (Jauker et al 2012a). Furthermore, several studies indicated that high amounts of OSR at the landscape scale have positive effects on solitary bees nesting in semi-natural habitats (Jauker et al 2012b; Diekötter et al 2014). However, foraging in agriculturally managed fields also enhances the risk of pollinating insects to be exposed to PPPs, which might potentially harmful.…”
Section: Introductionmentioning
confidence: 99%